Find the sum of the values of
and
if
,
,
are in
and
,
and
are in
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
F r o m A P w e c a n w r i t e , ( 2 x + 1 ) − ( x + y ) = ( 3 x − 1 ) − ( 2 x + 1 ) = > x − y + 1 = x − 2 = > y = 1 + 2 S o , y = 3 F r o m G P w e c a n w r i t e , x x y = x y 3 x + 1 0 y = > y = x y 3 x + 1 0 y = > 3 = 3 x 3 x + 3 0 [ s i n c e , y = 3 ] = > 3 x = x + 1 0 = > 2 x = 1 0 S o , x = 5 N o w S u m o f x & y i s , x + y = 3 + 5 = 8 .